Selected contribution: Ventilatory response to CO2 in high-altitude natives and patients with chronic mountain sickness. - Fatemian, M; Gamboa, A; Léon-Velarde, F; Rivera-Ch, M; Palacios, J; Robbins, P (2003)
The ventilatory responses to CO(2) of high-altitude (HA) natives and patients with chronic mountain sickness (CMS) were studied and compared with sea-level (SL) natives living at SL. A multifrequency binary sequence (MFBS) in end-tidal Pco(2) was employed to separate the fast (peripheral) and slow (central) components of the chemoreflex response. MFBS was imposed against a background of both euoxia (end-tidal Po(2) of 100 Torr) and hypoxia (52.5 Torr). Both total and central chemoreflex sensitivity to CO(2) in euoxia were higher in HA and CMS subjects compared with SL subjects. Peripheral chemoreflex sensitivity to CO(2) in euoxia was higher in HA subjects than in SL subjects. Hypoxia induced a greater increase in total chemoreflex sensitivity to CO(2) in SL subjects than in HA and CMS subjects, but peripheral chemoreflex sensitivity to CO(2) in hypoxia was no greater in SL subjects than in HA and CMS subjects. Values for the slow (central) time constant were significantly greater for HA and CMS subjects than for SL subjects.